EFFICACY OF DIFFERENT FUNGICIDES AGAINST FUSARIUM SOLANI CAUSING CORIANDER ROOT ROT - C. M. BHALIYA; K. B. JADEJA (The Bioscan, 2014)
Different contact, systemic and combination of fungicides were evaluated in vitro against Fusarium solani. Amongst contact (non systemic) fungicides evaluated maximum inhibition in mycelial growth was observed in mancozeb (100%) and zineb (100%) followed by chlorothalonil (72.52%). Among the different concentrations tried, Mancozeb and Zineb gave 100% inhibition at all concentration, while chlorothalonil gave 80.28% growth inhibition followed by copper oxychloride (79.25%) at 2500 ppm concentration. Out of six systemic fungicides, carbendazim found best with 98.68% mycelial growth inhibition followed by propiconazole (85.27%) and difenoconazole (75.53%). Carbendazim showed complete inhibition of mycelial growth of the test fungus at 500 ppm concentration followed by same fungicide with 250 ppm (99.46%) and 100 ppm (98.12%). Among the fungicides combination, cymoxanil + mancozeb, carbendazim + mancozeb and Tricyclazole + mancozeb gave 100% growth inhibition at all concentration followed by carboxin + thirum with 98.79% mean growth inhibition while least inhibition was observed in Zineb + Hexaconazol (72.19%).